ANALISIS PENGGUNAAN MATERIAL KOMPOSIT CFRP PADA STRUKTUR SUBFLOOR PESAWAT PADA KASUS FOUR POINT BENDING - Dimas Nur Hadian Shah, Wahyu
This research discusses about four-point bending load that happened on sub o- or model of A320 airplane which modelled using Carbon Fiber Reinforced Plas- tic/Polymer (CFRP) Material. At rst, CFRP is only used in aerospace and avia- tion industry because of its relatively high price. But now, even automotive industry is starting to use CFRP material from sports car to Formula 1's car. Increasement in CFRP material usage is caused by the properties of CFRP itself which is light weight but doesn't really reduce the strength of the structure signicantly. We can conclude that the usage of CFRP material can be used across all industry. So it's important to understand what are the eect of CFRP material usage when loaded with four-point bending case. In order to achieve the objective of the research, sub oor's responses in four- point bending loading using CFRP material is analyzed using numerical analysis. In order to simulate four-point bending case, in this simulation we modelled four cylinders where two cylinders below the sub oor which are puncher1 and puncher2 represent two shock absorber below the sub oor of A320 that serve to push the sub o- or upward and two cylinders on top of the sub oor which are support1 and support2 represent the joint between sub oor and frame and serve to hold the sub oor when the impact landed on the sub oor. According to those numerical simulation, we could get some conclusion which are bending crush behavior will be dierent from one another. It depends on the thickness and conguration of orientation angle of composite ber. Then bending collapse resistance and the strength of the structure are aected by orientation angle of composite ber. Increasing orientation angle of composite ber results in increasement of bending collapse resistance by 10.87% from orientation angle of 30 degree to 45 degree and 18% from 45 degree to 75 degree. Futhermore increasing ber orientation angle of composite will increase the strength of the structure itself by 13.22% from 30 degree to 45 degree and 4.76% from 45 de- gree to 75 degree. And the last one is thickness is very in uental signicantly on the strength and bending collapse resistance of the structure. If we increase the thickness from 3 mm to 6 mm we will get increasement of the bending collapse resistance by 8.51% and strength of the structure by 153.77%. There is a hope that this research could be used as base consideration of using CFRP composite material, In sub oor structure of aircraft particularly and in other industies in general.